2,4-Dihydroxy-5-Nitropropiophenone Oxime as an Analytical Reagent: Studies on Cobalt Chelate - Kumar B. Patel, Nitin; K. Desai, K. (Asian Journal of Chemistry, 2010)
2,4-Dihydroxy-5-nitropropiophenone oxime (DHNPO) has been used as an analytical reagent for gravimetric and spectrophotometric determination of Co(II). Metal-ligand ratio (1:2) has been determined using spectrophotometric method. Stability constant of complex has been calculated. The complex was found paramagnetic in nature. TGA studies were done on complex. Energy of activation for decomposition steps has been calculated, using Broido method.